2012
DOI: 10.1007/s00285-012-0635-5
|View full text |Cite
|
Sign up to set email alerts
|

The robustness of phase-locking in neurons with dendro-dendritic electrical coupling

Abstract: We examine the effects of dendritic filtering on the existence, stability, and robustness of phase-locked states to heterogeneity and noise in a pair of electrically coupled ball-and-stick neurons with passive dendrites. We use the theory of weakly coupled oscillators and analytically derived filtering properties of the dendritic coupling to systematically explore how the electrotonic length and diameter of dendrites can alter phase-locking. In the case of a fixed value of the coupling conductance (g c ) taken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…We modified a previous single-compartment striatal FSI model [47] by adding a dendritic compartment (shown to be an important determinant of gap-junction mediated synchrony [48][49][50][51]) and increasing the conductance of the D-type K current to 6 mS/cm 2 . Previous work showed that two characteristic attributes of FSI activity in vitro, stuttering and γ resonance (defined as a minimal tonic firing rate in the γ frequency range), are dependent on the D-current [30,47].…”
Section: Single Model Fsis Produce δ/θ-Nested γ Rhythms Whose Power Amentioning
confidence: 99%
See 1 more Smart Citation
“…We modified a previous single-compartment striatal FSI model [47] by adding a dendritic compartment (shown to be an important determinant of gap-junction mediated synchrony [48][49][50][51]) and increasing the conductance of the D-type K current to 6 mS/cm 2 . Previous work showed that two characteristic attributes of FSI activity in vitro, stuttering and γ resonance (defined as a minimal tonic firing rate in the γ frequency range), are dependent on the D-current [30,47].…”
Section: Single Model Fsis Produce δ/θ-Nested γ Rhythms Whose Power Amentioning
confidence: 99%
“…The current study focuses on the oscillatory bands frequently observed in striatal local field potential: δ (1-3 Hz), θ (4-7 Hz), β (8-30 Hz), low γ (50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60), and high γ (70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80) [10,16,28]. Power in these bands consistently correlates with responses to task parameters including motor initiation, decision making, and reward [10][11][12]20].…”
Section: Introductionmentioning
confidence: 97%
“…Dendritic electrical synapses are often not enough to induce temporally sharp spike synchrony, perhaps because of their weakness or locations distant from spike-generating zones (axon initial segments in many neurons) (Saraga et al, 2006;Lewis and Skinner, 2012;Schwemmer and Lewis, 2014). Active conductances in dendrites (Johnston and Narayanan, 2008) may enhance or suppress the phase-locking effects of electrical synapses.…”
Section: Electrical Synapses Can Mediate Phase-locking Synchrony Anmentioning
confidence: 99%
“…In fact, antisynchrony among electrically coupled model neurons is particularly sensitive to the shapes of action potentials and the intrinsic membrane conductances that underlie them (Chow and Kopell, 2000;Nomura et al, 2003;Pfeuty et al, 2003). Antisynchronous states are often quite fragile, particularly as the sites of electrical synapses move more distally, away from spike-generating zones (Schwemmer and Lewis, 2014).…”
Section: Electrical Synapses Can Mediate Phase-locking Synchrony Anmentioning
confidence: 99%
“…A number of theoretical works dealt with understanding the essential components responsible for such synchrony or failure of synchrony among electrically coupled neurons, some of them using relaxation oscillator models [9, 15, 11], and others using integrate-and-fire model neurons [16, 17, 18, 19]. The latter approach is based on the widely successful theory of weakly coupled oscillators [20, 21, 22, 23, 24] that requires specification of the coupling mechanism including the voltage time course and the neuron’s phase response curve (PRC). A knowledge of these two elements is sufficient to completely predict when and why a set of identical neurons synchronize.…”
Section: Introductionmentioning
confidence: 99%